The Easiest Way to Learn Russian as A Foreign Language - Abdualieva D.R.; Sharipova N.I. - (Zien Journals, 2021)
This article notes how it is easier and faster to master the Russian language, especially the spoken language. What needs to be done for this, what methods to master, what way to find a way out for yourself, based on your capabilities and desires.
Keywords: language; USSR; Facebook; motivation